Ǧärmän dägg näw ‘Deutsches/Deutschland ist gut!’: Ein amharisches Lied zu Ehren des deutschen Kaisers aus der Sammlung Kaschke - Voigt, Rainer (Aethiopica, 2004)
As a member of the Deutsche Aksum-Expedition (1905/06) Dr. Erich Kaschke – while in Aksum in 1906 – produced a series of cylinder recordings which today are held in the Ethnologisches Museum (formerly: Museum für Völkerkunde) in Berlin. From Kaschke’s collection of “Abyssinian Phonogrammes” Song No. 5, which is here analyzed, represents a song of praise to the German Kaiser (Wilhelm II) due to whose decisive intervention the German Aksum Expedition was to become reality so quickly. In this Amharic song the German Kaiser is seen as the promise of the Fǝkkare Iyyäsus as well as participating in the line of David and Solomon, the father of Menelik I, the progenitor of the Ethiopian dynasty. In this way a connection with the then Ethiopian Emperor Menelik II was procured.